Principlism and communitarianism - Callahan, D (Journal of medical ethics, 2003)
The decline in the interest in ethical theory is first outlined, as a background to the author’s discussion of principlism. The author’s own stance, that of a communitarian philosopher, is then described, before the subject of principlism itself is addressed. Two problems stand in the way of the author’s embracing principlism: its individualistic bias and its capacity to block substantive ethical inquiry. The more serious problem the author finds to be its blocking function. Discussing the four scenarios the author finds that the utility of principlism is shown in the two scenarios about Jehovah’s Witnesses but that when it comes to selling kidneys for transplantation and germline enhancement, principlism is of little help.